ARTISTIC LITERATURE - EDUCATOR OF A PERFECT GENERATION (Academicia Globe: Inderscience Research, 2023)
The article highlights the importance of fiction in educating the future of our country, the young generation, its role in the education of the nation, as well as the issues of strengthening the faith of the intellectual generation of our country, instilling national identity through fiction.